Professional Identity Transition of Vocational Graduates: Adaptive Strategies of Session Musicians in Jakarta - Mohamad Alfiah Akbar; Oki Rahadianto Sutopo; Hajar Pamadhi (Institut Seni Indonesia Yogyakarta, 2025)
Session musicians occupy a unique position as mobile and flexible professionals who must be able to adapt to diverse musical situations while facing unstable economic and social pressures. The transition from formal education to an industry that demands multidimensional competencies often becomes a highly challenging phase, where the artistic idealism of graduates meets a competitive and unpredictable reality. This study aims to understand the transition of graduates from the Vocational Program in Music Performance toward a career as session musicians in Jakarta’s music industry. The main focus of this research is to reveal the challenges faced by the graduates and the adaptive strategies they develop to sustain their careers. This research employs a qualitative case study approach within the framework of grounded theory. Data were collected through in-depth interviews and both participatory and non-participatory observations involving fourteen informants, consisting of music college graduates, community musicians, producers, and music directors. Data analysis was conducted through open coding, axial coding, and selective coding to identify thematic categories. The results show that formal education provides a technical foundation but does not fully prepare graduates to face the fluid and uncertain realities of the industry. Conversely, adaptive strategies such as cross-genre musical flexibility, non- formal learning through mentoring and observation, personal branding, reputation management, networking, and technological adaptation emerge as key competencies determining career success. These findings affirm that the resilience of session musicians is shaped not only by technical skills but also by social, symbolic, and cultural capital developed beyond formal education. Theoretically, this study expands the discussion on musicians’ professional identity and the precarity of creative labor in Indonesia. Practically, it implies the need to strengthen the vocational music curriculum to emphasize not only musical skills but also professional networking, entrepreneurship, and digital literacy to better prepare graduates for the competitive music industry.